2021
DOI: 10.3389/fcimb.2021.691538
|View full text |Cite
|
Sign up to set email alerts
|

Wide Application of Minimally Processed Saliva on Multiple RT-qPCR Kits for SARS-CoV-2 Detection in Indonesia

Abstract: Saliva as a sample matrix has been an attractive alternative for the detection of SARS-CoV-2. However, due to potential variability in collection and processing steps, evaluating a proposed workflow amongst the local population is recommended. Here, we aim to validate the collection and treatment of human saliva as a direct specimen for RT-qPCR-based detection of SARS-CoV-2 in Indonesia. We demonstrated that SARS-CoV-2 target genes were detected in saliva specimens and remained stable for five days either refr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In this study, we utilized saliva specimens, which allows for a more convenient sampling process. We validated the pooling-of-four method toward heat-treated saliva specimens, an RNA-extraction-free method previously described by Mahendra et al [ 6 ]. A study by Watkins et al pooled 5, 10, and 20 saliva specimens prior to RNA extraction and RT-qPCR detection of SARS-CoV-2 and reported a decrease in sensitivity of 7.41%, 11.11%, and 14.81%, respectively [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we utilized saliva specimens, which allows for a more convenient sampling process. We validated the pooling-of-four method toward heat-treated saliva specimens, an RNA-extraction-free method previously described by Mahendra et al [ 6 ]. A study by Watkins et al pooled 5, 10, and 20 saliva specimens prior to RNA extraction and RT-qPCR detection of SARS-CoV-2 and reported a decrease in sensitivity of 7.41%, 11.11%, and 14.81%, respectively [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that the addition of Proteinase K may help to reduce the viscosity of saliva specimens [8,34,35]. However, this is still equivocal, as other prior studies also indicated that the addition of Proteinase K did not improve the outcome of testing using saliva specimens [6,36]. Further study might be needed to find a solution to this problem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations